Environmental Crimes of Early Romanian Communism: Focus on the Enemies of Agriculture - Petrişor, Alexandru-Ionuţ; Tîrzman, Elena (Problemy Ekorozwoju, 2019)
The early beginning of the communist regime in Romania was influenced by transformations of agriculture (including husbandry and fishing), forced to develop intensively (replacing traditional technologies with mechanical ones) and extensively (by taking over natural systems, such as the wetlands). Since the yield did not increase as expected, the conflict with nature was aggravated by finding enemies among the species situated at the top of food chains, blamed for the losses. In order to expedite the outcomes of fighting against these species, media campaigns were developed in parallel with awards given to hunters and people who became part of the war. This paper attempts to correlate the environmental impact of campaigns against certain species with the loss of biodiversity based on statistical data. The analysis indicated that there were direct campaigns to eliminate species conflicting with economy and collateral victims. Each case study illustrates a different point; bustards were eliminated by carelessness (although protected, their status was not enforced); the pelican was eliminated due to insufficient knowledge and contrasting recommendations; and wolf was sentenced to death consciously. The results indicate that although many authors parallel nowadays communist and environmentalist policies, the real communist practices had a strong deleterious environmental impact despite a pro-environmentalist appearance.